Successful transportation of wild stock of endangered "Thooli" (Labeo dussumieri) spawners without anaesthetics - Gopalakrishnan, A; Ponniah, A G; Basheer, V S; Padmakumar, K G; Krishnan, Anuradha; Lal, Kuldeep K (Indian Journal of Fisheries, 2011)
Several problems are encountered during transportation of fishes from wild to captivity. The note describes successful transportation of wild caught endangered Labeo dussumieri spawners over distances below 100 km without anesthesia or sophisticated transporting devices which is of immense help in the gene banking programme of endangered species